PENGARUH PEMBIAYAAN MURABAHAH DANPEMBIAYAAN MUSYARAKAHTERHADAP PROFITABILITAS DENGAN NON PERFORMING FINANCING SEBAGAI VARIABEL INTERVENING (PADA BANK UMUM SYARIAH PRIODE 2018-2021) - Fitri Nurul Hidayah (Program Studi Ekonomi Syariah Sekolah Tinggi Agama Islam Negeri Mandailing Natal, 2023)
This study aims to determine the effect of Murabahah financing and Musyarakah financing on profitability (ROA) with Non Performing Financing (NPF) as an intervening variable in Islamic Commercial Banks for the 2018-2021 period. The data used in this study is secondary data, namely in the form of quarterly reports of Islamic Commercial Banks for the 2018-2021 period. The population in this study is Islamic Commercial Banks in Indonesia, the sampling technique in this study was carried out using a purposive sampling method. This research is descriptive with quantitative research. The analytical method used in this study was multiple regression analysis and path analysis which were processed using an analytical tool, namely IBM SPSS Statistics 24 software. The results of this study indicate that Murabahah financing has an effect on the profitability of Islamic Commercial Banks, Musyarakah financing has an effect on the profitability of Islamic Commercial Banks, Non Performing Financing (NPF) has an effect on the profitability of Islamic Commercial Banks, Murabahah financing has an effect on Non Performing Financing (NPF) of Islamic Commercial Banks, Murabahah financing affects Non Performing Financing (NPF) of Islamic Commercial Banks, Non Performing Financing (NPF) can mediate between Murabahah financing and profitability (ROA) of Sharia Banks, and Non Performing Financing (NPF) can mediate between Musyarakah financing and profitability (ROA) Sharia Commercial Banks.